Common Fixed Point Results for a Pair of Generalized Nonlinear Mappings in Complete Metric Spaces (Journal of Mathematical Study, 2025)
In this paper, under the asymptotically regular condition, we investigate theexistence of a unique common fixed point for a pair of generalized nonlinear mappingsin the framework of complete metric spaces. Additionally, we extend our analysis tothe case involving two control functions. Our work generalizes some results in recentpapers.